Now it’s up to the Architects Return to Drawing - Nicola di Battista (Diségno)
If it is true, as we said to write two year ago in the editorial in the magazine Domus, that we are at the beginning of a new season, then what is most important for us to understand is how to approach and how to take part in that season, what role we want to play in it and above all whether we want to determine it, even only partly, or be subjected to it. This thinking concerns us from at least two points of view: one that concerns every one of us as individuals, and the other collectively, due to the craft, the profession that we practise as part of a community.